Analysis of the phytochemical content and the antibacterial, antifungal and antioxidant activities of the roots, stems and leaves of Hemidesmus indicus, Ocimum sanctum and Tinospora cordifolia - Visweswara Rao. P; Sujana. P; Vijaykanth. T; Sankar. N.S.; Vijaya kumar. B.; Naidu. D.; Gan. S.H. (Asian Network for Scientific Information, 2013)
Hemidesmus indicus (H. indicus), Ocimum sanctum (O. sanctum) and Tinospora cordifolia (T. cordifolia) are three important medicinal plants in traditional Indian medicine. In this study, the methanolic and chloroform extracts of different plant parts (roots, stems and leaves) of H. indicus, O. sanctum and T. cordifolia were subjected to phytochemical, antibacterial, antifungal and antioxidant tests. Phytochemical screening of both extracts of each plant part revealed the presence of phytochemicals such as alkaloids, flavonoids, phenolic compounds, steroids and tannins. The methanolic extracts of all three plants exhibited greater antibacterial and antioxidant effects than the chloroform extracts. These effects could be related to the high content of phytochemical constituents such as alkaloids, steroids, tannins, flavonoids and phenols. When comparing the various plant parts, the roots of H. indicus had the highest number of antimicrobial activities, showing antibacterial properties against all of the investigated organisms except for one (A. flavus). The H. indicus leaf extract had antibacterial activities against S. aureus, E. coli and K. pneumoniae while the stem was effective against P. vulgaris and A. niger. The root of T. cordifolia has the second highest antimicrobial activity, acting against five different organisms (B. subtilis, S. aureus, K. pneumoniae, P. vulgaris and A. niger). O. sanctum leaf extract exhibits antibacterial activity against B. subtilis and E. coli, while the stem is only effective against B. subtilis. The methanolic root and stem extracts of H. indicus, the methanolic leaf extract of O. sanctum and the stem extract of T. cordifolia also have antioxidant potential.